From Concept to Practice: Implementing Sustainable Tourism Development at Anurak Community Lodge in Thailand - SMITH, Scott (Journal of Environmental Management and Tourism; Vol 14 No 4 (2023): JEMT, Volume XIV, Issue 4(68), Summer 2023DO - 10.14505/jemt.14.4(68).22, 2023)
This study investigates the integration of responsible tourism practices in Anurak Community Lodge's business model in southern Thailand, using a mixed-methods approach that combines field research, in-depth interviews, and guest surveys. The findings suggest that responsible tourism positively impacts the sustainability of the tourism industry and offers practical recommendations for implementing sustainable practices. The study highlights the importance of engagement, staff training, and environmental management in the successful implementation of responsible tourism. The results can inform policies and guidelines for sustainable tourism development and can be used by tourism operators to promote responsible tourism. The study should be of interest to various stakeholders committed to responsible tourism and will contribute to the body of knowledge, particularly in light of the COVID-19 pandemic's impact on the tourism industry.